Re-modelling the quality of urban life (QOUL) index for Kuala Lumpur city, Malaysia - Mohit, Mohammad Abdul; Hj. Mohd. Noor, Norzailawati; Zahari, Rustam Khairi; Abdul Malek, Nurhayati (Research Management Center, International Islamic University Malaysia, 2016)

(untitled)
This research developed a QOL framework with seven components - economic ability, housing condition, functional environment, safety condition, social and community participation, physical and emotional health and spiritual life, to explore the quality of life in six strategic zones - City Centre (CC), Wangsa Maju Maluri (WMM), Sentul Menjalara (SNTL-M), Damansara-Penchala (DM-PNC), Bukit Jalil-Seputeh (BJ-SPT) and Bandar Tun Razak-Sungai Besi (BTR-SB) of KL City. A QOL questionnaire with 100 variables was developed and administered in the six zones. Sample households were selected based on the house types. The survey questionnaire was administered in the six neighborhoods of KL – CC-200, WMM-200, SNTL-M-311, DM-PNC-260, BJ-SPT-211 and BTR-SB-331. Sample households were selected based on house types. Collected data were analyzed by using both descriptive and inferential statistics. The findings of the research indicate that on many socio-economic aspects, the residents of the six zones of KL are different and these differences are responsible to their perceptual evaluation on their QOL. The residents of KL including the residents of WMM, SNTL-M and BTR-SB are unsatisfied (Mean≥3.5) while the residents of CC, DM-PNC and BJ-SPT are slightly satisfied (Mean<3.0).with their economic abilities/ conditions. Again, whereas the residents of KL along with the residents of WMM, SNTL-M, BTR-SB and DM-PNC are slightly satisfied, the residents of CC and BJ-SPT are moderately satisfied (Mean≥3.5-<4.0) with their housing condition. Furthermore, whereas KL residents along with CC and DM-PNC residents are fairly satisfied, the residents of WMM, SNTL-M and BTR-SB are slightly satisfied with their functional environment. Only the residents of BJ-SPT are moderately satisfied with the component. The residents of KL including the residents of CC, SNTL-M and DM-PNC are slightly satisfied while the residents of BJ-SPT are moderately satisfied but the residents of WMM and BTR-SB are unsatisfied with their safety environment. With regard to Social and Community Participation, the residents of all six neighbourhoods are slightly satisfied with that component. Concerning physical and emotional health, the residents of KL along with the residents of SNTL-M, DM-PNC are moderately satisfied while the residents of CC, WMM, BTR-SB and BJ-SPT are slightly satisfied with that component. Further, with regard to spiritual life, whereas the residents of KL along with the residents of CC, WMM, BTR-SB, DM-PNC and BJ-SPT are moderately satisfied, the residents of SNTL-M are fairly satisfied with the component. Concerning the residents’ overall assessment with their QOL, it is observed that the residents of KL along with the residents of BJ-STP, DM-PNC, SNTL-M and WMM assessed their QOL as moderately good (Mean≥3.5) while the residents of CC and BTR-SB assessed their QOL as slightly good (Mean≥3.0-<3.5). The research concludes that the residents of six strategic zones of KL City perceived their QOL based on the objective conditions that prevail in each zone. Therefore, improving the objective conditions that cover economic ability, housing condition, functional environment, safety condition and social/ community participation while maintaining the physical facilities that support physical and emotional health and spiritual life of the residents in each zone, can help enhance the residents’ QOL condition in the city.